Peran Guru Bimbingan dan Konseling dalam Kurikulum Merdeka Sebagai Upaya untuk Meminimalisir Bullying di Sekolah - Nuraeni Nuraeni; I Wayan Widiana; I Gede Ratnaya (Jurnal Paedagogy, 2023)
The research aims to analyze the role of guidance and counseling teachers in minimizing bullying in schools. The research method used a systematic literature review with a qualitative approach. The data source of this research were obtained from articles and books that discussed bullying and the role of teachers. Data analysis techniques in this study used content or content analysis. The results of this study indicated that teacher guidance and counseling played a central role in preventing bullying behavior in schools. This role is clearly stated in the implementation of the independent curriculum. In addition, guidance and counseling teachers must actively provide services to students in preventive and curative efforts to prevent bullying.